Strategi Komunikasi Perumdam Tirta Tarum Dalam Mencapai SDGS No. 6: Clean Water And Sanitation - Aulia Rachman, Muhammad Wildan; Kusumaningrum, Rastri; Nurkinan, Nurkinan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this study aims to describe how Perumdam Tirta Tarum designs a communication strategy in supporting the achievement of SDGs number 6 related to the provision of clean water and sanitation. To describe the process of implementing the SDGs campaign number 6 run by Perumdam Tirta Tarum in an effort to provide access to clean water and sanitation that is decent and sustainable. And to identify factors that support and hinder the implementation of Perumdam Tirta Tarum's communication strategy in achieving SDGs target number 6. This research method uses a qualitative method. Data sources in this study come from two types of data, namely primary data obtained through in-depth interviews and observations. Then secondary data comes from available sources, including PERUMDAM's annual report which contains information about achievements, strategies, and programs related to clean water and sanitation, campaign materials such as brochures, pamphlets, social media content, and official documents and relevant statistics. The results of the study indicate that Perumdam Tirta Tarum's communication strategy in supporting SDGs number 6 is carried out through internal cross-unit coordination, even without formal written documents. Planning is flexible and adaptive, in line with Charles Berger's communication theory. The implementation of communication includes digital media and direct approaches to the community, with regular evaluation through public feedback. Supporting factors for this strategy include rapid response to complaints, an effective social media team, and external policy support. Barriers include limited internet in remote areas and difficulties in conveying technical language to the public. Substantially, this strategy supports the achievement of SDGs 6.1 and 6.b through the principles of adaptive, collaborative, and evaluative communication.)